High-throughput screening of RNA polymerase inhibitors using a fluorescent UTP analog - Bhat, Jyothi; Rane, Rajendra; Solapure, Suresh M.; Sarkar, Dhiman; Sharma, Umender; Harish, M. N.; Lamb, Sarah; Plant, Darren; Alcock, Peter; Peters, Steve; Barde, Shubhada; Roy, Raman K. (Journal of Biomolecular Screening, 2006)
RNA polymerase (RNAP) is a well-validated target for the development of antibacterial and antituberculosis agents. Because the purification of large quantities of native RNA polymerase from pathogenic mycobacteria is hazardous and cumbersome, the primary screening was carried out using Escherichia coli RNAP. The authors have developed a high-throughput screening (HTS) assay to screen for novel inhibitors of RNAP. In this assay, a fluorescent analog of UTP, gamma-amino naphthalene sulfonic acid (gamma-AmNS) UTP, was used as one of the nucleotide substrates. Incorporation of UMP in RNA results in the release of gamma-AmNS-PPi, which has higher intrinsic fluorescence than (gamma-AmNS) UTP. The assay was optimized in a 384-well format and used to screen 670,000 compounds at a concentration of 10 mu M. About 0.1% of the compounds showed more than 60% inhibition in the primary HTS. All the primary actives tested for dose response using the same assay had an EC50 below 100 mu M. Eighty percent of the primary HTS actives obtained using E. coli RNAP showed comparable activity against Mycobacterium smegmatis RNAP in the conventional radioactive assay. Activity of hits selected for the hit-to-lead optimization was also confirmed against Mycobacterium bovis RNAP which has > 99% sequence identity with Mycobacterium tuberculosis RNAP subunits.